Comparison of the ICare® rebound tonometer with the Goldmann tonometer in a normal population - Fernandes, Paulo Rodrigues (2005)
[Excerpt] Purpose: The aim of this study was to evaluate the accuracy of measurement of intraocular pressure (IOP) using a new induction/impact rebound tonometer (ICare®) in comparison to the Goldmann applanation tonometer (AT). [...]